Ontologies of Property: Land Titling after the Indian Ocean Tsunami Disaster. (1st October 2018) - Fitzpatrick, Daniel
Abstract : The 2004 Indian Ocean tsunami killed over 150, 000 people and displaced over 500, 000 in Indonesia alone. In the worst hit province of Aceh, the disaster damaged or destroyed almost all land-related records. The response included a World Bank-designed systematic land titling project. The Aceh case highlights a number of ontological assumptions of titling projects in natural disaster contexts, including that states are able to replace heterodox local processes with law; and that titling is a depoliticised technical process for the evidencing of existing legal rights to land. The article highlights the way in which the ontological framing of land titling is misplaced in dynamic circumstances of disaster involving urgent needs for shelter, and associated reconfigurations of property and human settlements.